A checklist of the water mites (Acari: Hydrachnidia) of India, with new records and description of one new species - Pešić, Vladimir; Chatterjee, Tapas; Bordoloi, Sabitry (Zootaxa, 2010)
Using published records and original data from recent research, a checklist was compiled of the water mite (Acari: Hydrachnidia) fauna of India. It includes 275 species in 70 genera and 25 families of water mites. The new records of 23 water mite species are reported; one species Wuria indica is described as new for science; a first description of the male is given for Wuria sumatrensis K. Viets, 1935. The present state of knowledge of the Indian water mite fauna is discussed.